2020
DOI: 10.1093/milmed/usz470
|View full text |Cite
|
Sign up to set email alerts
|

Change in Anthropometrics and Physical Fitness in Norwegian Cadets During 3 Years of Military Academy Education

Abstract: Introduction High physical fitness is associated with increased occupational performance, better health, and reduced risk of injuries in military personnel. Thus, the military emphasizes physical training to maintain or develop physical fitness in their soldiers. It is important to monitor the effect of the physical training regime, but such information is lacking for Norwegian military cadets. Hence, the primary aim of this study was to investigate changes in anthropometrics and physical fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(38 reference statements)
1
8
0
1
Order By: Relevance
“…Then, in the course of military studies, semester credits include strength tests, starting with hanging on a bar with arms bent, through marching and running with loads and ending with pull-ups on a bar and instrumental gymnastics. An adequate level of strength is a desirable motor ability that has been the subject of much research at other military academies and cadet training centres around the world [41][42][43][44][45]. The presence of strength in the regression analysis can be explained by the need for women to undertake strength training, as they are forced to put the most work into shaping their strength to meet the demands of daily military service.…”
Section: Discussionmentioning
confidence: 99%
“…Then, in the course of military studies, semester credits include strength tests, starting with hanging on a bar with arms bent, through marching and running with loads and ending with pull-ups on a bar and instrumental gymnastics. An adequate level of strength is a desirable motor ability that has been the subject of much research at other military academies and cadet training centres around the world [41][42][43][44][45]. The presence of strength in the regression analysis can be explained by the need for women to undertake strength training, as they are forced to put the most work into shaping their strength to meet the demands of daily military service.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study investigated prospective changes in physical fitness and anthropometrics of cadets with a similar 3-year follow-up period as used in the present study. 10 The investigated cadets were 3 years younger (~23 yrs. at baseline) than the participants in the present study, however,in line with the present study, Aandstad et al (2020) observed a decrease in aerobic fitness.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent study has shown in Norwegian male cadets that aerobic fitness decreased, while muscle power and muscular endurance increased, during their education period of 3-years. 10 Moreover, increased waist circumference and decreased sit up performance was observed in Air Force Reserve Officer` Training Corps (ROTC) cadets during the 4-year education, while push-up performance and aerobic fitness remained unchanged. 11 about what happens after graduation and during the early career of an officer.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have been conducted so far on the BC of air force personnel [ 1 , 2 , 3 ]. The BC of air force personnel might differ from that of army and navy personnel, reflecting the different physiological demands to which they are subjected [ 4 ]. This aspect showed that research findings in army and navy personnel cannot be applied to those in the air force.…”
Section: Introductionmentioning
confidence: 99%
“…BC depends on the aircrew’s job, with airplane pilots being taller, and having more total body water, intracellular water, extracellular water, proteins, minerals, soft lean mass, fat-free mass, and skeletal muscle mass than transport aircrew as well as lower body mass index (BMI) and body fat mass than transport aircrew [ 1 ]. So far, studies on the BC of air force personnel have focused on men’s groups, with fewer data reported on women [ 4 , 9 ]. BC is a health-related fitness component that differs between women and men for an average score.…”
Section: Introductionmentioning
confidence: 99%